2022
DOI: 10.3389/fphar.2022.996871
|View full text |Cite
|
Sign up to set email alerts
|

A novel phenolic derivative inhibits AHL-dependent quorum sensing signaling in Pseudomonas aeruginosa

Abstract: Increasing antibiotic resistance and the decline in the pharmaceutical industry’s investments have amplified the need for novel treatments for multidrug-resistant bacteria. Quorum sensing (QS) inhibitors reduce pathogens’ virulence without selective pressure on bacteria and provide an alternative to conventional antibiotic-based therapies. P. aeruginosa uses complex QS signaling to control virulence and biofilm formation. We aimed to identify inhibitors of P. aeruginosa QS acting on acyl-homoserine lactones (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…These AHLs bind to the transcriptional activators LasR and RhlR and activate target promoters. Both las and rhl have been implicated in the regulation of quinolone-like signaling molecule production in a group of Pseudomonas [29,30]. As C4-HSL and 3-oxo-C12-HSL are quinolone precursors, they could not be detected when quinolones were highly homogenously produced throughout the P. putida biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…These AHLs bind to the transcriptional activators LasR and RhlR and activate target promoters. Both las and rhl have been implicated in the regulation of quinolone-like signaling molecule production in a group of Pseudomonas [29,30]. As C4-HSL and 3-oxo-C12-HSL are quinolone precursors, they could not be detected when quinolones were highly homogenously produced throughout the P. putida biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…The final reaction mixture for RT PCR constitutes 10 μM of forward and reverse primer (1:1, 2 μL), RNase-free water (0.8 μL), and SYBER green (10 μL). The sequence of primers was referred from the reported literature , and listed in Table S4. The RT-PCR was performed as follows: one cycle at 95 °C for 30 s for initial denaturation, followed by 40 cycles, each cycle consisting of denaturation programmed at 95 °C for 30 s followed by annealing and extension at 60 °C for 30 s. The experiments were performed in triplicates.…”
Section: Methodsmentioning
confidence: 99%
“…Findings within this study revealed that most novel compounds were effective anti-bacterial agents, some compounds were potent inhibitors of biofilm formation, whereas compound UA3 has shared significant anti-quorum sensing potential against Chromobacterium pseudoviolaceum ( Rafiq et al., 2022 ). In the study performed by Bernabè et al. (2022) in house library of phenolic derivatives (81 compounds) were tested for anti-QS activity.…”
Section: Anti-virulence Potential Of Novel Compoundsmentioning
confidence: 99%